The Level of Literacy Obsolescence in the Thesis of Master Study Program of Management at Muhammadiyah University Hospital, Yogyakarta - Winata, Arda Putri; Ramawati, Yuliana (Record and Library Journal, 2018)
Background of the study: The level of obsolescence of references used in the thesis of the Master study program of Hospital Management. Purpose: The purpose of this study is to determine the level of obsolescence of the references used in the thesis of the Master study program of Hospital Management. Method: This study uses a quantitative descriptive method with a sample in the form of a student thesis Program Study of the Management at Muhammadiyah University Hospital Yogyakarta in 2017 totaling 48 pieces of theses. Findings: Data is displayed in a table with a description. Obtained the results of Md = 2009. Thus, the citation below the year 2009 with a total of 857 (43.5%) citation was declared obsolete, while the citation above the year 2009 with a total of 1112 (56.5%) was declared valid. Conclusion: From this explanation, it can be concluded that the level of obsolescence of literature in the thesis of the master's study program in the management of Muhammadiyah UniversityYogyakarta is obtained from Md = 2009. Then, the citation below in 2009 with a total of 857 (43.5%) citation was declared obsolete, while the citation above 2009 with a total of 1112 (56.5%) declared valid.